A method for preparing an electromagnetic impedance-tapered double-gradient-structure foam

CN114773657BActive Publication Date: 2026-10-23SICHUAN UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202210566921.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-24
Publication Date
2026-10-23
Estimated Expiration
2042-05-24

AI Technical Summary

Benefits of technology

(1)本发明合成工艺简单,合成时间较短,绿色环保,生产成本低,容易实现大批量生产;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114773657B_ABST
    Figure CN114773657B_ABST
Patent Text Reader

Abstract

The application discloses a preparation method of an electromagnetic impedance gradient double-gradient structure foam, which comprises three steps, the first step is to prepare a foaming precursor emulsion, the second step is to add isocyanate as a foaming component, and after high-speed stirring, in-situ foaming is carried out under an applied magnetic field, and the third step is to carry out a thermal imidization process at high temperature. Due to the attraction of the applied magnetic field to the magnetic wave-absorbing agent particles in the foam, the content of the wave-absorbing agent is gradually reduced with the increase of the distance from the magnetic field source, and a gradient distribution is formed. Due to the change of the content of the wave-absorbing agent, the foam matrix viscosity is changed, the foam pore size forms a gradient distribution, and then a double-gradient gradient structure is formed. The foam is favorable for improving the attenuation characteristics and further improving the impedance matching performance of the foam, solves the contradiction between the attenuation characteristics and the impedance matching performance, reduces the reflection of electromagnetic waves on the surface of the foam, and widens the effective wave-absorbing frequency band. Under the single-layer matching thickness, the effective wave-absorbing bandwidth is up to 10.7 GHz, and the foam has great application potential.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of microwave absorbing materials technology, specifically a method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure. Background Technology

[0002] In recent years, with the development of modern science and technology, intelligent communication and electronic technology have developed rapidly, and the potential hazards brought by electromagnetic radiation have become increasingly prominent. The research and development of absorbing materials that can attenuate electromagnetic radiation has become a research hotspot in materials science.

[0003] Given the current diversity of electromagnetic frequency bands, modern intelligent absorbing materials are required to possess multi-band absorption capabilities to maximize the attenuation of electromagnetic wave radiation. To meet the absorption requirements of different frequency bands, absorbing materials need to be able to absorb multiple frequency bands and have a wide bandwidth. Multilayer structures have the advantage of absorbing waves simultaneously in different bands; however, because multilayer structures are composed of discontinuous layers with different properties, the presence of interfaces significantly affects the impedance matching performance of the structure, thereby reducing its attenuation capability. Furthermore, the obvious interface combination is prone to debonding when faced with mechanical interference such as high-frequency vibrations, significantly reducing its durability and resulting in extremely high maintenance costs. Therefore, through reasonable absorbing foam structure design, relying on the precise control of material interfaces and components, and achieving a gradient transition in multilayer absorbing materials and structures, the aim is to maximize the incident and effective absorption of electromagnetic waves, thereby optimizing the foam's impedance matching performance and attenuation characteristics, and achieving the desired "thin, light, wide, and strong" effect for absorbing materials. This is currently the main research direction. Summary of the Invention

[0004] The purpose of this invention is to overcome the problems mentioned in the background art and to provide a method for preparing a foam with a gradually varying electromagnetic impedance dual gradient structure, which can produce high-quality foamed microwave absorbing materials.

[0005] The objective of this invention is mainly achieved through the following technical solutions: A method for preparing a foam with a gradually varying electromagnetic impedance dual gradient structure includes the following steps: (1) Dissolve 60-80g of aromatic dianhydride and alcohol in 50-60g of polar solvent, then add 5-10g of polyethylene glycol as a hydroxyl chain extender, then add 3-10g of amine catalyst and 2-5g of organotin catalyst, then add 10-20g of silicone oil and 10-15g of water, and stir continuously to obtain polyimide foaming precursor emulsion (PAA). During the continuous stirring process, add 0%-2% of magnetic absorbing agent according to the total mass of the system, sonicate for 30min, and then stir for 20min to make the absorbing agent uniformly dispersed in the emulsion, as component one; (2) Add 100-150g of isocyanate as component two to component one and stir continuously at a high speed of 2000-300rpm for 15s-30s. Pour it into a mold to allow it to foam freely. At the same time, adjust the distance of the external induced magnetic field source (from 0 to 150mm) so that the magnetic absorber exhibits a gradient distribution of content under the attraction of the gradually changing magnetic field. Meanwhile, the change in the absorber content from more to less causes the viscosity of the foam matrix to change from large to small in a synchronous and gradual manner, so that the foam pore size exhibits a gradient distribution, thereby realizing the construction of a double gradient structure. (3) After foaming, the foam is allowed to settle naturally at room temperature for 6 hours, then dried in a vacuum oven at 40°C for 12 hours. After that, it is kept at 80°C, 120°C and 180°C for 2 hours in the vacuum oven, and then cooled to room temperature in the vacuum oven to complete the thermal imidization, thus obtaining the polyimide foam material (PI foam) with a gradient electromagnetic impedance structure.

[0006] The current Chinese patent CN 107903430 A discloses a method for preparing isocyanate-based polyimide rigid foam, which belongs to the control process of prepolymer preparation, foaming process, and high-temperature post-treatment. Different foam materials with different structures and properties are obtained by adjusting the ratio of organotin catalysts and amine catalysts. However, in the preparation process, the prepolymer needs to react at 80℃~95℃ for 4~6 hours, which is difficult to meet the requirements for convenient and rapid preparation. Furthermore, it results in a homogeneous structure and does not evaluate or control the microwave absorption performance.

[0007] Chinese patent CN 113929955 A discloses a rigid polyimide foam and its preparation method. The method first prepares a polyimide foam precursor solution, then rapidly injects the polyimide foam precursor solution and a polyisocyanate compound into a high-pressure vessel, introduces high-pressure CO2, and performs wet gelation under high-pressure conditions. Finally, it uses supercritical CO2 to extract the polar solvent, obtaining a porous polyimide gel, which is then imidized to obtain polyimide foam. However, the preparation process requires raising the temperature of the high-pressure vessel to 31.1°C~100°C and the pressure to 7.52MPa~40MPa to maintain the supercritical state of CO2, resulting in significant energy consumption. Furthermore, the foam has a homogeneous structure, and its microwave absorption performance is not evaluated or controlled.

[0008] The literature (Materials Today Physics 2021, 21, 100521) discloses a method for preparing polyimide / carbon nanotube composite foam. The method involves rapidly stirring a polyimide foam precursor solution and a polyisocyanate compound, then pouring the mixture into a mold for free foaming, followed by imidization to obtain a homogeneous polyimide foam. Subsequently, a method of multiple impregnations with a carbon nanotube suspension is used to composite the polyimide and carbon nanotubes. However, the carbon nanotubes in the polyimide / carbon nanotube composite foam prepared by this method have weak bonding with the foam pore walls, making them prone to detachment under external forces and failing to meet long-term service requirements.

[0009] The purpose of this invention is to improve the one-step foaming process of polyimide using isocyanate and polyimide precursor emulsions. In this process, a microwave absorbing agent is added to the precursor emulsion and subjected to ultrasonic treatment to ensure uniform mixing. Then, the isocyanate component is added, and after high-speed stirring, a gradual magnetic field is applied during free foaming to induce a gradient distribution of the microwave absorbing agent and foam pore size, thereby forming a dual-gradient structure. This one-step synthesis process of polyimide using isocyanate and polyimide precursor emulsions is simple, efficient, and environmentally friendly as it does not produce harmful gases. The dual-gradient structure of electromagnetic and impedance properties improves the impedance matching performance of the foam material, further enhancing its electromagnetic wave attenuation capability, and can be applied in microwave absorption, electromagnetic shielding, and other fields.

[0010] The obtained polyimide foam material with a gradient electromagnetic impedance structure was mixed with polyethylene paraffin in a certain proportion and cut into a ring with an inner diameter of 3 mm and an outer diameter of 7 mm. The wave absorption performance of the composite material was obtained by using a vector network analyzer.

[0011] Furthermore, the aromatic dianhydride includes one or more of pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenyl methyl ether tetracarboxylic dianhydride, 2,2-bis(3,4-phthalic anhydride)hexafluoropropane, or 1,3-bis(3,4-phthalic anhydride)hexafluoropropane. The aromatic rings in the aromatic dianhydride selected in this scheme contribute to the molecular chain strength and thermodynamic stability. Simultaneously, the aromatic dianhydride and isocyanate groups can undergo a polycondensation reaction, and the small molecules produced in the reaction act as a blowing agent, giving the polyimide material a porous structure.

[0012] Furthermore, the alcohols include one or more of methanol, ethanol, or ethylene glycol. This scheme selects alcohols as chain extenders, which react with the functional groups on the isocyanate chain to extend the molecular chain, increase the molecular weight, and improve the mechanical and processing properties of products such as polyimide.

[0013] Furthermore, the polar solvent includes one or more of tetrahydrofuran, dimethylformamide, dimethylacetamide, or N-methylpyrrolidone. This foaming system is relatively large; using such amine-containing polar solvents provides good solubility and is beneficial for increasing the foaming chemical reaction rate.

[0014] Furthermore, organotin catalysts include one or more of dibutyltin diacetate, dibutyltin dilaurate, or stannous octoate. The organotin compounds selected can coordinate with isocyanate ions, polarizing the -NCO group, thereby making the positively charged carbon atoms in the isocyanate molecule more reactive and more readily reacting with the terminal hydroxyl groups of the polyol polymer.

[0015] Furthermore, amine catalysts include one or more of triethanolamine, triethylamine, triethylenediamine, dimethylaminoethyl ether, dimethylaminoethoxyethanol, and triethylenediamine. Amine catalysts readily react with isocyanates, tightly linking to the polymer backbone, thus not only catalyzing foaming but also acting as effective crosslinking agents or chain extenders.

[0016] Furthermore, the amount of microwave absorbing agent added is 1%-2% of the total mass of the system. At this content, the microwave absorbing agent exhibits good intrinsic electromagnetic loss capability and impedance matching characteristics, demonstrating excellent microwave absorption effect.

[0017] Furthermore, the magnetic absorbing agent comprises a composite material of flake-shaped carbonyl iron powder, magnetite, or ferrite. The key to achieving the dual-gradient structure in this method is the directional induction of the magnetic absorbing agent under a magnetic field environment. Simultaneously, this type of magnetic absorbing agent has readily available raw materials, facilitates the preparation of composite materials, and exhibits good absorption performance.

[0018] Furthermore, the isocyanate includes one or more of polyphenyl polymethylene polyisocyanate, phenyl dimethylene diisocyanate, toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, or meta- or p-1,4-methylphenylmethylene diisocyanate. These isocyanates are all aromatic dianhydrides, and the resulting polyimide exhibits thermal and mechanical stability.

[0019] Furthermore, the aromatic dianhydride is pyromellitic dianhydride, the alcohol is methanol, the polar solvent is dimethylformamide, the organotin catalyst is dibutyltin dilaurate, the amine catalyst is triethanolamine, and the isocyanate is polyphenyl polymethylene polyisocyanate.

[0020] In summary, the present invention has the following advantages compared with the prior art: (1) The synthesis process of this invention is simple, the synthesis time is short, it is green and environmentally friendly, the production cost is low, and it is easy to achieve mass production; (2) The electromagnetic impedance gradient dual-gradient structure foam material synthesized in this invention has good impedance matching performance and electromagnetic wave attenuation characteristics, and can be used in electromagnetic shielding, microwave absorption, high-density information magnetic recording and other fields. Attached Figure Description

[0021] The accompanying drawings, which are included to provide a further understanding of embodiments of the invention and form part of this application, do not constitute a limitation thereof. In the drawings: Figure 1 This is a schematic diagram of the dual-gradient impedance gradient foam structure of the present invention.

[0022] Figure 2 This is a SEM image of the dual-gradient foam structure of the present invention.

[0023] Figure 3 This is a diagram showing the wave absorption performance of the dual-gradient structure foam of the present invention. Detailed Implementation

[0024] To make the objectives, technical solutions, and advantages of the present invention clearer, the present invention will be further described in detail below with reference to the embodiments and accompanying drawings. The illustrative embodiments and descriptions of the present invention are only used to explain the present invention and are not intended to limit the present invention.

[0025] Example 1: like Figures 1-3 As shown, 74g of pyromellitic dianhydride and 12g of methanol were dissolved in 55g of N-dimethylformamide. Then, 10g of polyethylene glycol, 3g of triethanolamine, and 2g of dibutyltin dilaurate were added sequentially, followed by 20g of silicone oil and 12g of water. While continuously stirring, a 1% (w / w) magnetic absorbing agent (carbon nanotube-coated iron oxide) was added. After sonication for 30 minutes, the mixture was stirred for another 20 minutes to ensure uniform dispersion of the absorbing agent in the emulsion, forming component one. Next, 100g of polyphenylene polymethylene polyisocyanate was added as component two and stirred vigorously for approximately 15 seconds. The mixture was then poured into a mold to allow free foaming. Simultaneously, the distance between the external induced magnetic field source and the foam was adjusted at a constant speed (5 mm / min). After foaming, the foam was allowed to settle naturally at room temperature for 6 hours, then dried in a vacuum oven at 40°C for 12 hours. It was then held at 80°C, 120°C, and 180°C for 2 hours each, and finally cooled naturally to room temperature to complete thermal imidization, thus obtaining a polyimide foam material with a gradient electromagnetic impedance structure. The final foam exhibited a minimum reflection loss of −18.9 dB and a maximum effective absorption bandwidth of 4 GHz.

[0026] Example 2: like Figures 1-3As shown, 74g of pyromellitic dianhydride and 12g of methanol were dissolved in 55g of N-dimethylformamide. Then, 10g of polyethylene glycol, 3g of triethanolamine, and 2g of dibutyltin dilaurate were added sequentially, followed by 20g of silicone oil and 12g of water. While continuously stirring, a 1.5% (w / w) magnetic absorbing agent (carbon nanotube-coated iron oxide) was added. The mixture was sonicated for 30 minutes, then stirred for another 20 minutes to ensure uniform dispersion of the absorbing agent in the emulsion, forming component one. Next, 100g of polyphenylene polymethylene polyisocyanate was added as component two and stirred vigorously for approximately 15 seconds. The mixture was then poured into a mold to allow free foaming. Simultaneously, the distance between the external induced magnetic field source and the foam was adjusted at a constant speed (5 mm / min). After foaming, the foam was allowed to settle naturally at room temperature for 6 hours, then dried in a vacuum oven at 40°C for 12 hours. It was then held at 80°C, 120°C, and 180°C for 2 hours each, and finally cooled naturally to room temperature to complete thermal imidization, thus obtaining a polyimide foam material with a gradient electromagnetic impedance structure. The resulting foam exhibited a minimum reflection loss of −42 dB and a maximum effective absorption bandwidth of 10.7 GHz.

[0027] Example 3: like Figures 1-3 As shown, 74g of pyromellitic dianhydride and 12g of methanol were dissolved in 55g of N-dimethylformamide. Then, 10g of polyethylene glycol, 3g of triethanolamine, and 2g of dibutyltin dilaurate were added sequentially, followed by 20g of silicone oil and 12g of water. While continuously stirring, a magnetic absorbing agent (carbon nanotube-coated iron oxide) with a mass fraction of 1.75% was added. After sonication for 30 minutes, the mixture was stirred for another 20 minutes to ensure uniform dispersion of the absorbing agent in the emulsion, forming component one. Next, 100g of polyphenylene polymethylene polyisocyanate was added as component two and stirred vigorously for approximately 15 seconds. The mixture was then poured into a mold to allow free foaming. Simultaneously, the distance between the external induced magnetic field source and the foam was adjusted at a constant speed (5 mm / min). After foaming, the foam was allowed to settle naturally at room temperature for 6 hours, then dried in a vacuum oven at 40°C for 12 hours. It was then held at 80°C, 120°C, and 180°C for 2 hours each, and finally cooled naturally to room temperature to complete thermal imidization, thus obtaining a polyimide foam material with a gradient electromagnetic impedance structure. The final foam exhibited a minimum reflection loss of −41 dB and a maximum effective absorption bandwidth of 8.9 GHz.

[0028] Example 4: like Figures 1-3As shown, 74g of pyromellitic dianhydride and 12g of methanol were dissolved in 55g of N-dimethylformamide. Then, 10g of polyethylene glycol, 3g of triethanolamine, and 2g of dibutyltin dilaurate were added sequentially, followed by 20g of silicone oil and 12g of water. While continuously stirring, a 2% (w / w) magnetic absorbing agent (carbon nanotube-coated iron(III) oxide) was added. The mixture was sonicated for 30 minutes, then stirred for another 20 minutes to ensure uniform dispersion of the absorbing agent in the emulsion, forming component one. Next, 100g of polyphenylene polymethylene polyisocyanate was added as component two and stirred vigorously for approximately 15 seconds. The mixture was then poured into a mold to allow free foaming. Simultaneously, the distance between the external induced magnetic field source and the foam was adjusted at a constant speed (5 mm / min). After foaming, the foam was allowed to settle naturally at room temperature for 6 hours, then dried in a vacuum oven at 40°C for 12 hours. It was then held at 80°C, 120°C, and 180°C for 2 hours each, and finally cooled naturally to room temperature to complete thermal imidization, thus obtaining a polyimide foam material with a gradient electromagnetic impedance structure. The resulting foam exhibited a minimum reflection loss of −45 dB and a maximum effective absorption bandwidth of 6.8 GHz.

[0029] Comparative Example 1: 74g of pyromellitic dianhydride and 12g of methanol were dissolved in 55g of N-dimethylformamide. Then, 10g of polyethylene glycol, 3g of triethanolamine, and 2g of dibutyltin dilaurate were added sequentially, followed by 20g of silicone oil and 12g of water. The mixture was stirred continuously until a homogeneous emulsion was formed, which became component one. Next, 100g of polyphenylene polymethylene polyisocyanate was added as component two and stirred vigorously for approximately 15 seconds. The mixture was then poured into a mold and allowed to foam freely. After foaming, the foam was allowed to settle naturally at room temperature for 6 hours, then dried in a vacuum oven at 40℃ for 12 hours. Finally, it was kept at 80℃, 120℃, and 180℃ for 2 hours each, and then naturally cooled to room temperature to complete thermal imidization, yielding the polyimide foam material. The final foam exhibited no microwave absorption properties.

[0030] Comparative Example 2: 74g of pyromellitic dianhydride and 12g of methanol were dissolved in 55g of N-dimethylformamide. Then, 10g of polyethylene glycol, 3g of triethanolamine, and 2g of dibutyltin dilaurate were added sequentially, followed by 20g of silicone oil and 12g of water. While continuously stirring, a magnetic microwave absorbing agent (carbon nanotube-coated flake carbonyl iron powder) with a mass fraction of 1.75% was added. The mixture was sonicated for 30 minutes, then stirred for another 20 minutes to ensure uniform dispersion of the microwave absorbing agent in the emulsion, forming component one. Next, 100g of polyphenylene polymethylene polyisocyanate was added as component two and stirred vigorously for approximately 15 seconds. The mixture was then poured into a mold to allow free foaming. After foaming, the foam was allowed to settle naturally at room temperature for 6 hours, then dried in a vacuum oven at 40℃ for 12 hours. Finally, it was kept at 80℃, 120℃, and 180℃ for 2 hours each, and then naturally cooled to room temperature to complete thermal imidization, yielding the polyimide microwave absorbing foam material. The final foam reflection loss was a minimum of -18 dB, and the widest effective absorption bandwidth was 2 GHz.

[0031] By comparing the examples and comparative examples, it is concluded that compared to foam structures without magnetic absorbing agents, the addition of a certain amount of magnetic absorbing agent can improve the electro / magnetic synergistic loss mechanism of the absorbing foam, thus contributing to the improvement of its absorption capacity. The introduction of a magnetic field environment enables the directional induction of the foam structure, ultimately resulting in a dual-gradient electromagnetic impedance structure without interfaces. The integrated gradient foam avoids durability issues caused by interface debonding. Simultaneously, the gradient distribution of the magnetic absorbing agent and the foam structure maximizes electromagnetic wave incidence and effective absorption, thereby optimizing the foam's impedance matching performance and attenuation characteristics, achieving the desired "thin, light, wide, and strong" effect for the absorbing material.

[0032] The above specific embodiments further illustrate the purpose, technical solution, and beneficial effects of the present invention. It should be understood that the above are merely specific embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.

Claims

1. A method for preparing a foam with a gradually varying electromagnetic impedance and a dual gradient structure, characterized in that, Includes the following steps: (1) Dissolve 60-80g of aromatic dianhydride and alcohol in 50-60g of polar solvent, then add 5-10g of polyethylene glycol as a hydroxyl chain extender, then add 3-10g of amine catalyst and 2-5g of organotin catalyst, then add 10-20g of silicone oil and 10-15g of water, and stir continuously to obtain polyimide foaming precursor emulsion. During the continuous stirring process, add 1%-2% of magnetic absorbing agent according to the total mass of the system, sonicate for 30min, and then stir for 20min to make the absorbing agent uniformly dispersed in the emulsion, as component one; (2) Add 100-150g of isocyanate as component two to component one and stir continuously at a high speed of 300-2000rpm for 15s-30s. Pour it into a mold to allow it to foam freely. At the same time, adjust the distance of the external induced magnetic field source so that the magnetic absorber exhibits a gradient distribution of content under the attraction of the gradually changing magnetic field. Meanwhile, the change in the content of the absorber from more to less causes the viscosity of the foam matrix to change from large to small in a synchronous and gradual manner, so that the foam pore size exhibits a gradient distribution, thereby realizing the construction of a double gradient gradient structure. (3) After foaming, the foam is allowed to settle naturally at room temperature for 6 hours, then dried in a vacuum oven at 40°C for 12 hours. After that, it is kept at 80°C, 120°C and 180°C for 2 hours in the vacuum oven, and then cooled to room temperature in the vacuum oven to complete the thermal imidization, thus obtaining the foam material with a gradient electromagnetic impedance structure.

2. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The aromatic dianhydride includes one or more of pyromellitic dianhydride, 3,3',4,4'-benzophenone tetracarboxylic dianhydride, 3,3',4,4'-diphenylmethyl ether tetracarboxylic dianhydride, 2,2-bis(3,4-phthalic anhydride)hexafluoropropane, or 1,3-bis(3,4-phthalic anhydride)hexafluoropropane.

3. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The alcohols include one or more of methanol, ethanol, or ethylene glycol.

4. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The polar solvent includes one or more of tetrahydrofuran, dimethylformamide, dimethylacetamide, or N-methylpyrrolidone.

5. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The organotin catalyst includes one or more of dibutyltin diacetate, dibutyltin dilaurate, or stannous octoate.

6. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The amine catalyst includes one or more of triethanolamine, triethylamine, triethylenediamine, dimethylaminoethyl ether, dimethylaminoethoxyethanol, and triethylenediamine.

7. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The distance of the external induced magnetic field source is 0 to 150 mm.

8. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The magnetic absorbing agent includes a composite material of flake carbonyl iron powder, iron oxide, or ferrite.

9. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The isocyanate includes one or more of polyphenyl polymethylene polyisocyanate, phenyl dimethylene diisocyanate, toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, or meta- or p-1,4-methylphenylmethylene diisocyanate.

10. The method for preparing a foam with a gradually varying electromagnetic impedance dual-gradient structure according to claim 1, characterized in that: The aromatic dianhydride is pyromellitic dianhydride, the alcohol is methanol, the polar solvent is dimethylformamide, the organotin catalyst is dibutyltin dilaurate, the amine catalyst is triethanolamine, and the isocyanate is polyphenyl polymethylene polyisocyanate.

Citation Information

Patent Citations

  • Hard polyimide foam and preparation method thereof

    CN113929955A

  • Preparation method of isocyanate based polyimide hard foam

    CN107903430A

  • Flame-retardant wave-absorbing polyimide foam material as well as preparation method and application thereof

    CN112745502A